Optimal sandwich panel's core design for an enhanced impact resistance - Assil Charkaoui; Noha M. Hassan; Zied Bahroun (Heliyon)
Despite the extensive literature revealing various core structures that can enhance the impact resistance of composite panels, a comparative study illustrating the difference in performance of the various cores under same loading conditions is missing. The aim of this study is to determine the optimal core structure and design in terms of energy absorption under low-velocity impact using both numerical simulations and experimental testing for validation. Response surface analysis was used to design the experiments and analyse the panel's behaviour. A total of 160 numerical simulations were conducted by varying the core shape, density, number of layers and panel's thickness. Drop tower tests were performed to experimentally validate the results. Additive manufacturing was used to 3D print the tested structures which simplified the manufacturing process. Results provided insights on time to perforation, stiffness of the panels showcasing an inverse relationship between recoverable strain energy and equivalent plastic strain. The number of layers within the panels were identified as a pivotal factor in the energy distribution and tendency for localized plastic deformation to occur. Both numerical and experimental results revealed the superior energy absorption capabilities of the X-frame core shaped structure. Regression models developed shed light on the relationships between core height, volume fraction, number of layers, and core topology revealing the extent of damage. Multi-objective optimization was used to yield optimal configuration for sandwich panels with highest impact resistance.